2021
DOI: 10.1007/s10792-021-01837-7
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of peripheral OCT imaging using a novel integrated SLO ultra-widefield imaging swept-source OCT device

Abstract: Purpose To describe the feasibility of peripheral OCT imaging in retinal diseases using a novel full-field device. Methods A total of 134 consecutive eyes were referred and imaged on the Optos Silverstone swept-source OCT (SS-OCT) (Optos PLC; Dunfermline, UK). Scanning laser ophthalmoscope (SLO) images and the associated SS-OCT images were obtained in the posterior pole, mid-periphery or far periphery based on the nature of the referral and on new areas of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…Indeed, in a case series of 125 eyes, Sodhi et al found that eighty-six out of 125 eyes (69%) had peripheral retinal lesions. Therefore, the UWF-OCT can provide further information on the area that cannot be visualized by standard OCT devices with a 50-degree field of view, thus providing a holistic clinical picture, which can potentially aid in understanding the various retinal pathologies [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in a case series of 125 eyes, Sodhi et al found that eighty-six out of 125 eyes (69%) had peripheral retinal lesions. Therefore, the UWF-OCT can provide further information on the area that cannot be visualized by standard OCT devices with a 50-degree field of view, thus providing a holistic clinical picture, which can potentially aid in understanding the various retinal pathologies [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another Optos OCT device, the Optos’ Monaco ® (Optos PLC, Dunfermline, UK), integrates UWF imaging with SD-OCT for a 200-degree single-capture image in less than 0.5 s [ 95 ]. Integration of these advances to capture the peripheral retina allows for peripheral OCT of retinal diseases including retinal tears, retinal holes, retinoschisis, retinal tuft, lattice degeneration, CSCR, choroidal nevi, and choroidal lesions ( Figure 7 ) [ 96 ].…”
Section: Wide-field and Ultrawide-field Oct (Wf-oct And Uwf-oct)mentioning
confidence: 99%
“…( C ) A retinal detachment in the peripheral retina. Reprinted with permission from Sodhi et al [ 96 ]. Feasibility of peripheral OCT imaging using a novel integrated SLO ultra-widefield imaging swept-source OCT device.…”
Section: Figurementioning
confidence: 99%
“…The ultrawide-field OCTA is the SS-OCT–based imaging system of ocular fundus structure and vasculature. The ultrawide-field OCTA devices currently employed in the clinic include Xephilio OCT-S1 (Canon) ( Takahashi et al, 2019 ), PLEX Elite™ 9000 (Carl Zeiss Meditech) ( Ledesma-Gil et al, 2021 ), Silverstone™ (Optos) ( Sodhi et al, 2021 ), and Triton™ DRI (Topcon) ( Sun et al, 2019 ). MHz FDML SS-OCT system (Optores) has high scan speed; however, it has not been approved for clinical application ( Tan et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%